Investigating the detection of parent-child relationships in early childhood: The role of partiality in resource distributions - McPhee, Anna Michelle; Bagh, Sinamys; Schmuckler, Mark A.; Sommerville, Jessica A. (Frontiers in Psychology, 2022)
By early childhood, children possess clear expectations about how resources should be, and typically are, distributed, expecting and advocating for equal resource distributions to recipients. Moreover, recent evidence suggests that children may be able to use deviations from equality in resource distributions to make inferences about the nature of social relationships. Here, we investigated whether children use partiality in resource distributions displayed by adults toward children in third-party contexts to identify parent-child relationships, whether children anticipate preferential treatment based upon knowledge of third-party parent-child relationships, and whether children anticipate different emotional reactions to impartiality in resource distributions in parent-child interactions compared to neighbor-child interactions. Four- to seven-year-old children were presented with hypothetical vignettes about an adult character who distributed resources to two children either equally, or systematically favoring one child. By the age of 4, children used resource distribution partiality to identify an adult as a child’s parent, and also used these expectations to guide their anticipated emotional reactions to impartiality. By the age of 6, children were also more likely to anticipate partiality to be displayed in parent-child compared to neighbor-child relationships. The findings from the current study reveal that partiality in resource distributions acts as a valuable cue to aid in identifying and understanding social relationships, highlighting the integral role that resources play in children’s understanding of their social world. More broadly, our findings support the claim that children use cues that signal interpersonal investment to specify and evaluate parent-child relationships in third-party contexts.